Application of a glassy carbon electrode modified with poly(glutamic acid) in caffeic acid determination - Santos, D. P.; Bergamini, M. F.; Fogg, A. G.; Zanoni, Maria Valnice Boldrin [UNESP] (Springer, 2005)
Glassy carbon electrodes were coated with films of poly( glutamic acid) ( PG), and the modified electrode proved to be very effective in the oxidation of caffeic acid. The performance of the film was also tested with ascorbic acid, coumaric acid, ferulic acid, sinapic acid and chlorogenic acid. At pH 5.6, all the hydroxycinnamic acids yield a higher peak current intensity when oxidized after incorporation in the PG-modified electrode, and only the oxidation of ascorbic acid exhibits overpotential reduction. At pH 3.5 only caffeic and chlorogenic acid are incorporated in the modified electrode and exhibit a well-defined oxidation wave at +0.51 V and +0.48 V, which is the base for their determination. Linear calibration graphs were obtained from 9 x 10(-6) mol L-1 to 4 x 10(-5) mol L-1 caffeic acid by linear voltammetric scan and from 4 x 10(-6) mol L-1 to 3 x 10(-5) mol L-1 by square wave voltammetric scan. The method was successfully applied to the determination of caffeic acid in red wine samples without interference from other hydroxycinnamic acids or ascorbic acid.
Keywords: hydroxycinnamates; caffeic acid; poly(glutamic acid); modified electrode